ANALISIS MUATAN NILAI KARAKTER PEDULI SOSIAL PADA TEKS CERITA PENDEK DALAM BUKU TEMATIK KELAS IV SD - Siti Nur Shaleha, - (2020)
This research is motivated by the problem of the importance of the role of teaching materials applied to the learning process in shaping and developing the character of students in grade IVth primary school. Through character education as the formation of social care values, it aims to mandate students about the importance of character education as a means of shaping behavior, and character education has a social dimension to create a social system that is good for the growth of every individual. Through the activities of forming the value of the character of social care by providing good moral education to students, namely by telling stories, some students like to listen to interesting stories, because the basic nature of students is that they always want to know new things, and telling stories can also broaden their horizons. In students by way of thinking. This study uses a qualitative research approach with content analysis research methods. Sources of data used are thematic books of grade IV elementary school students, instruments used are based on indicators contained in Darmiatun (in Utami, Alfriandra, Waluyati, 2019, page. 21), namely help, tolerance, tolerance, social action, and morality noble. The results showed that the short story text in the thematic books of grade IV SD contained values of social caring characters. So the short story text is one of the media that is very well used in the cultivation of character education in students that can be used in learning at school and at home. Short story texts can also be used to convey the subject matter to be conveyed to students.